The importance of applying the method of homogeneous sections in determining the cost of health service in public hospitals - The case study of the hospital Baj sisters_ Chlef Algiers - - Barbari, Mohamed Amine; Boulahia, Tayeb (Dirassat Journal Economic Issue, 2019)
The introduction of more effective methods in the management and away from administrative and classical management, the Algerian public hospitals must introduce cost accounting as a tool for management and the cost of hospital service. The most important methods of cost accounting that we see serve the objectives of the Algerian hospital and are in line with the possibilities and conditions available, We find the method of homogeneous sections, trying to highlight the economic dimension and methodology applied in the institution under study to enable us to determine the cost of hospital service received by the patient.